Removal capability, implant-abutment connection damage and thermal effect using ultrasonic and drilling techniques for the extraction of fractured abutment screws: an in vitro study - María Bufalá Pérez; Álvaro Zubizarreta-Macho; Javier Borrajo Sánchez; Jorge Hernández Rodríguez; Jorge Alonso Pérez-Barquero; Elena Riad Deglow; Sofía Hernández Montero (BMC, 2022)
Abstract The aim of this work was to analyze and compare the removal capability, conical internal hex implant-abutment connection damage and thermal effect using ultrasonic and drilling techniques for the extraction of fractured abutment screws. Twenty abutment screws were randomly fractured into twenty dental implants and randomly extracted using the following removal techniques: Group A: drilling technique without irrigation (n = 10) (DT) and Group B: ultrasonic technique without irrigation (n = 10) (UT). The dental implants were submitted to a preoperative and postoperative micro-computed tomography (micro-CT) scan to obtain a Standard Tessellation Language (STL) digital file that determined the wear comparison by morphometry. Moreover, the thermographic effects generated by the DT and UT removal techniques were registered using a thermographic digital camera. Comparative analysis was performed by comparing the volumetric differences (mm3) between preoperative and postoperative micro-CT scans and thermographic results (°C) using the Student t test. The DT extracted 8/10 and the US 9/10 abutment screws. The pairwise comparison revealed statistically significant differences between the volumetric differences of postoperative and preoperative micro-CT scans of the DT (− 0.09 ± − 0.02mm3) and UT (− 0.93 ± − 0.32mm3) study groups (p = 0.0042); in addition, the pairwise comparison revealed statistically significant differences between the thermographic values of the DT (38.12 ± − 10.82 °C) and UT (78.52 ± 5.43 °C) study groups (p < 0.001). The drilling technique without irrigation provides a less removal capability, less conical internal hex implant-abutment connection damage and less thermal effect than ultrasonic technique for the extraction of fractured abutment screws; however, the ultrasonic technique resulted more effective for the extraction of fractured abutment screws.